Advancement in automation of co-extrusion collagen casings - Barbut, Shai (Frontiers in Soft Matter, 2024)
Co extrusion sausage technology has been a game changer in the industry as it transformed the traditional way of filling meat betters into premade casings (e.g., materials such as cellulose or natural casings) to producing the casings on top of the meat batter as it comes out of the stuffer. This allows full automation of the process (working 24/7) with lower waste, while also increasing food safety standards. The main material used is collagen which today is extracted from a limited type of beef hides. It is then treated with a strong alkaline solution, to breakdown some of the original structures, and later with a strong acid to allow swelling of the resulting suspension. The application of the collagen gel requires special equipment to line up the collagen fibers in such a way that they provide the strength and elasticity during the cooking operation (meat expends during cooking) and later provide the consumer with the characteristics bit / 'snap' similar to natural casings. Understanding the interactions between the chemical and physical properties of collagen is essential in obtaining good results. During production it is important that the collagen is quickly dried and crosslinked so the shape of the product will not be modified. This requires special large horizontal dryers and a unit to apply liquid smoke (source of aldehydes for crosslinking). Currently most systems are built for large capacity production, and therefore require large investment, however the industry is working on developing smaller and more flexible units for future use.